The yellow birds [compact disc, unabridged] : a novel - Powers, Kevin (Hachette Audio, 2012)
In Al Tafar, Iraq, 21-year-old Private Bartle and 18-year-old Private Murphy cling to life as their platoon launches a bloody battle for the city. In the endless days that follow, the two young soldiers do everything to protect each other from the forces that press in on every side: the insurgents, physical fatigue, and the mental stress that comes from constant danger.